IMPROVING COMPLIANCE WITH ELECTRONIC POSITIVE PATIENT AND POSITIVE ACCESSION IDENTIFICATION DURING ABORH SPECIMEN COLLECTION IN A TERTIARY HOSPITAL: A QUALITY IMPROVEMENT INITIATIVE - Aylward, Brigid; Elamin, Rehab; Ford, Jason; Yousef, Atef; Bibawi, Hani; Karim, Mohammed Yousuf; Almiski, Mohammed Sadek; Carl Niclas Bjorkhammer; Eileen McBride (International Journal of Patient Safety and Quality, 2025)
Background Errors in patient and specimen identification during ABORh specimen collecting are critical causes of transfusion-related adverse events. “Wrong blood in tube” (WBIT) incidents remain a preventable risk in clinical practice despite existing verification processes and systems. Therefore, accurate patient and accession identification is essential in transfusion services to avoid blood mismatch errors. Methods This project used a quasi-experimental pre–post quality improvement design guided by the Institute for Healthcare Improvement (IHI) Model for Improvement and implemented through two Plan–Do–Study–Act (PDSA) cycles. Baseline data from 2023 were compared with post-implementation data collected through September 2025. Results Compliance improved from 62.7% (n = 4,663 baseline) to 99.4% (n = 4,063 post-implementation). The improvement was highly significant (χ² = 1,811.41, p < 0.001). Improvement trends began in June 2024 and have remained to-date. Conclusions  A combined approach of system optimization, education, and real-time feedback via dashboard monitoring led to a substantial and durable increase in correct patient and specimen identification. This model may be replicable in other settings to enhance transfusion safety.